Effect of a black garlic extract combined with ascorbic acid on the colour and lipid oxidative stability of patties - Nuria Fernández Fernández-Valladares; Irma Caro; Javier Mateo; Mauricio Fernando Mariño Almache (Tecnociencia Chihuahua)
Oxidation of meat products limits their quality and shelf life and is prevented by antioxidant additives. Natural ingredients rich in antioxidants are proposed as an alternative to these additives. In this study, the antioxidant effect of an aqueous extract of black garlic, as a natural ingredient rich in polyphenols, was evaluated in pork patties. 20 ml of extract, obtained from a homogenate prepared with one-part garlic and three parts water, was used per kg of patty in combination with three levels of ascorbic acid (from 0.125 to 0.5 g/kg). The effect of different combinations to prevent discolouration in raw patties and lipid oxidation stability in cooked patties during aerobic refrigerated storage was tested. The use of black garlic extract darkened the patties and increased the red and yellow indices. Ascorbic acid potentiated the antioxidant effect of black garlic in cooked patties and vice versa. The black garlic extract combined with ascorbic acid, even in an amount four times lower than that commonly used in the meat industry, was the treatment with the highest antioxidant effect.